Synthesis of Rh-MOF/PVA-PVP nanofibers for skin cancer and infection inhibition - Ali Altharawi; Taibah Aldakhil; Manal A. Alossaimi (Frontiers in Chemistry)
Using electrospinning for nanofiber production, we can create unique materials with multiple applications in various industries, including medical bandages and wound dressings. One of the most important features of these materials and using the electrospinning technique, is the incorporation of compounds and metals into their structure. In this study, a new metal-organic framework (MOF) was synthesized from rhodium, a metal with significant biological potential, which was then used to produce new nanofibers using electrospinning technique, (Rh-MOF/PVA-PVP nanofiber) by mixing polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP). The newly synthesized nanofiber was tested against common microbial skin pathogens and cancer cells, showing significant inhibition. Specifically, an IC50 value of 19.45 μg/mL against cancer cells and MIC values ranging from 4 μg/mL to 64 μg/mL μg against skin pathogenic strains were observed. This notable inhibitory ability can be attributed to both physical characteristics (with specific surface area of 2,348 m2/g), and chemical factors, including the active compounds present in its rhodium (Rh) structure. The synthesized Rh-MOF/PVA-PVP nanofiber has the potential for use in developing bioactive bandages, and wound dressings.